Structural, Electronic, Mechanical and Optical Properties of RhZrZ (Z = As, Sb) Half-Heusler Compounds: First-Principles Calculations - Adem Beriso Bejo; Megersa Wodajo Shura; Mesfin Asfaw Afrassa; Kumneger Tadele; Fekadu Tolessa Marem; Kunsa Haho Habura (Advances in Condensed Matter Physics)
In this study, density functional theory (DFT) as it is implemented in the Quantum Espresso simulation package was employed to investigate the structural, electronic, mechanical and optical properties of RhZrZ (Z = As, Sb) half-Heusler compounds. Results reveal that both the two compounds are most stable in α phase. Analysis of mechanical properties shows that the compounds are ductile in nature and mechanically stable. Calculations of band structure and density of states indicated that they are semiconductors with RhZrAs direct and RhZrSb indirect band gap. Furthermore, the investigation of the optical properties reveals that there is a high absorption coefficient and low electron energy loss in visible and some ultraviolet energy spectrum indicating that these compounds are potential candidates for optoelectronic applications.